Pott's puffy tumour: innovative technique in calvarial reconstruction. Issue 11 (7th October 2019) - Mettias, B; Dow, G; Srinivasan, D; Ramakrishnan, Y
Abstract: Background: Pott's puffy tumour is a rare complication of sinusitis. This osteomyelitis can affect the outer and inner tables of the frontal sinus. The treatment of Pott's puffy tumour combines medical and surgical approaches. Surgical approaches have traditionally been open, but endoscopic techniques have been adopted recently in select cases. The bony defect from debridement can be left alone, or closed with autografts or allografts. Objective: To describe a technique for the reconstruction of a large skull vault after the debridement of extensive osteomyelitis of the anterior cranial vault. Methods: Modified distraction osteogenesis is used in the cranial vault, to induce new bone formation. This is customarily used to lengthen long bones. The advantages of this technique include avoiding autologous grafts or alloplastic cranioplasty in the infected surgical bed, and allowing primary closure. Results: Early post-operative imaging results have been encouraging, with no reported complications. Conclusion: Modified distraction osteogenesis is a novel technique in the primary reconstruction of calvarial bone.